2020
DOI: 10.1038/s41467-020-17129-0
|View full text |Cite|
|
Sign up to set email alerts
|

C9orf72 arginine-rich dipeptide repeats inhibit UPF1-mediated RNA decay via translational repression

Abstract: Expansion of an intronic (GGGGCC) n repeat region within the C9orf72 gene is a main cause of familial amyotrophic lateral sclerosis and frontotemporal dementia (c9ALS/FTD). A hallmark of c9ALS/FTD is the accumulation of misprocessed RNAs, which are often targets of cellular RNA surveillance. Here, we show that RNA decay mechanisms involving upstream frameshift 1 (UPF1), including nonsense-mediated decay (NMD), are inhibited in c9ALS/FTD brains and in cultured cells expressing either of two arginine-rich dipept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 49 publications
5
68
0
Order By: Relevance
“…Recent studies have demonstrated that UPF1 expression can modulate DPR- or HRE-induced degenerative phenotypes in various OE models of C9-ALS ( Ortega et al, 2020 ; Sun et al, 2020 ; Xu et al, 2019 ). To validate this, we utilized a Drosophila melanogaster model of C9orf72 ALS that expresses 30 G 4 C 2 repeats (30R) upstream of a polyadenylation signal ( Xu et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that UPF1 expression can modulate DPR- or HRE-induced degenerative phenotypes in various OE models of C9-ALS ( Ortega et al, 2020 ; Sun et al, 2020 ; Xu et al, 2019 ). To validate this, we utilized a Drosophila melanogaster model of C9orf72 ALS that expresses 30 G 4 C 2 repeats (30R) upstream of a polyadenylation signal ( Xu et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of multiple RNA metabolism pathways has been observed as a result of the HRE. Recently, three groups have published apparently discordant findings that nonsense-mediated decay (NMD) is either inhibited ( Sun et al, 2020 ; Xu et al, 2019 ) or upregulated ( Ortega et al, 2020 ) in different C9-ALS model systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our understanding of DPR-related toxicity has been augmented through the use of codon-optimized constructs expressing each DPR independent of G 4 C 2 repeats ( May et al, 2014 ; Mizielinska et al, 2014 ; Jovicic et al, 2015 ). Although poly-GA is the most abundant DPR localizing in p62-positive inclusions in postmortem tissues from C9ORF72 ALS/FTD patients, multiple lines of evidence suggest that arginine-rich DPRs are the most toxic of the five DPRs in both in vitro and in vivo disease models ( May et al, 2014 ; Mizielinska et al, 2014 ; Moens et al, 2019 ; Cook et al, 2020 ; Sun et al, 2020 ).…”
Section: Dprs the Gain Of Toxic Function: Clues From Different Modelmentioning
confidence: 99%
“…Similarly, overexpression of GFP-GR 100 in HEK293T cells induced the formation of stress granules and delayed their disassembly as compared to HEK293T cells overexpressing GFP alone (Zhang et al, 2018 ). A recent study demonstrated that expression of polyGR and polyPR in transfected HeLa cells induced stress granule formation, with polyGR and polyPR expression causing stress granules to form in 45% of cells and 24% of cells, respectively (Sun et al, 2020 ).…”
Section: Effects Of Methylating Arginine On Membraneless Organellesmentioning
confidence: 99%